Soil compaction alleviation by deep non - inversion tillage and crop yield responses in no tilled soils of the Pampas Region of Argentina. A meta - analysis - Peralta, Guillermo Ezequiel; Alvarez, Carina Rosa; Taboada, Miguel Angel (Elsevier, 2021)
No till is considered part of the good management practices recommended in conservation agriculture. Regardless of the benefits of this practice, shallow compaction or soil hardening by farm machinery traffic can lead to soil constraints to crop growth. Deep non-inversion tillage could be proposed together with other practices to alleviate this soil compaction. In this meta-analysis, we reviewed experimental results (32 field studies) obtained throughout the Pampas Region focused on the immediate effects and duration of soil mechanical alleviation measured by relevant soil physical properties and by the impact on maize and soybean yield. Treatments were classified in: a) Control (no tilled soils), and b) Subsoiled (no tilled soil subjected to mechanical compaction alleviation by deep non-inversion tillage). Data were analyzed by comparing pairs of the same experiment (t-paired test). The response to compaction alleviation (Δ Subsoiled - Control) for different soil variables was related to soil and climate and agricultural history management. Deep non-inversion tillage significantly decreased soil bulk density (0− 0.20 m; P < 0.0001; -4.3 % in average), increased infiltration rate fivefold (Δ = +213 mm.h− 1) and decreased soil penetration resistance in the 0− 0.20 m layer 44 % in average (Δ = -0.86 MPa). Soil penetrometer resistance profiles (0 to 0.4 m) of Control situations peaked at 0.15− 0.20 m. This peak disappeared in deep tillage, showing significant penetration resistance decreases at these layers. Soil compaction alleviation works had a durability of not more than 17 months (±2.8 months) after being performed. Deep non-inversion tillage enhanced soybean yields (26 % on average; Δ = +561 kg. ha− 1; P < 0.0001), mainly in yields lower than 2000 kg. ha− 1, usually associated with clay soils. In maize, mean responses to deep non- inversion tillage were only 6% (Δ = +567 kg. ha− 1; P < 0.0001). Considering these results, deep non- inversion tillage could be a promising practice to close rainfed crop yield gaps in the region. Nevertheless, due to its low durability in time, it is strategic to incorporate further compaction prevention and structural regeneration practices such as cover crops, diversified crop rotations and controlled traffic according to soil and environment characteristics